Human information processing : an introduction to psychology - Lindsay, Peter H.; Norman, Donald A. (Academic Press, 1972)
Human Information Processing: An Introduction to Psychology aims to convey the excitement of modern experimental psychology to the beginning student. The book discusses the organization of auditory perceptions; neural information processing; and the theories of pattern recognition. The text also describes the visual system; the dimensions of vision; the auditory system; and the dimensions of sound. The neural basis of memory; transient memories; the structure of memory; and memory processes are also considered. The book further tackles language acquisition; the process of learning and cognitiv.